Canary in a coal mine: How trade concerns at the Goods Council reflect the changing landscape of trade frictions at the WTO - Roy Santana; Adeet Dobhal (World Trade Organization (WTO), 2024)
This paper studies the under-explored yet critical role of WTO's regular bodies, particularly focusing on the discussions of "trade concerns" within the Goods Council, its subsidiary bodies, as well as the General Council. These discussions are pivotal for the governance of international trade and are key in resolving trade frictions among WTO Members, going beyond the conventional realms of diplomatic negotiation and legal adjudication. By scrutinizing trade concerns deliberated within these bodies over the past 29 years, this paper provides insights into their indispensable function in enhancing policy transparency, facilitating constructive dialogue on trade measures, and offering a platform for members to voice concerns over the trade practices of others. Our analysis, based on a new methodology that focuses on the number of interventions rather than the number of trade concerns, uncovers a growing trend where Members are increasingly leveraging these discussions to navigate and mitigate trade tensions, even amidst institutional challenges such as the Appellate Body impasse, and illustrates how different groups of Members participate in these bodies. This phenomenon underscores the Goods Council's strategic position within the WTO structure, above the technical bodies and below its most political body, which has enabled it to become a useful barometer for the shifting dynamics of global trade frictions.
Keywords: F02; F13; F53; F55; K33; 330; Economic cooperation; Goods Council; trade concerns; specific trade concerns (STCs); trade disputes; trade frictions; transparency; development; trade diplomacy; WTO governance